Облік та управління дебіторською заборгованістю для зміцнення фінансової безпеки підприємства - Бардадим, Марія Василівна; Bardadym, Mariya; Свічкар, Наталія Михайлівна; Svichkar, Nataliia (Мукачівський державний університет Видавничий дім «Гельветика», 2023)
Стаття присвячена аналізу сучасних підходів до обліково-аналітичного забезпечення процесу управління дебіторською заборгованістю з метою зміцнення фінансової безпеки підприємств України. Аналіз статистичних даних свідчить про нарощування обсягів дебіторської заборгованості підприємствами України, що обумовлює необхідність пошуку інструментів управління її структурою та стимулювання швидкості сплати рахунків дебіторами. У статті надано приклади застосування міжнародного формату обліку дебіторської заборгованості, торгівельний векселів до отримання та методів нарахування резерву сумнівних боргів. Проаналізовані можливості та переваги використання мотиваційних знижок, торгівельних векселів до отримання як інструментів оптимізації структури дебіторської заборгованості. Надано порівняльний аналіз методів резервування сумнівної дебіторської заборгованост. The article is devoted to the analysis of modern approaches to the accounting and analytical support of the receivables management process in order to strengthen the financial security of Ukrainian enterprises. The analysis of statistical data shows the increase in the amount of accounts receivable by Ukrainian enterprises, which makes it necessary to find tools for managing its structure and stimulating the speed of payment of accounts by debtors. The active transition of Ukrainian enterprises to the application of international reporting standards and the European integration vector of Ukraine's development requires the use of accounting methods and debt management tools that are successfully used in international and European practice. The article provides examples of the application of the international accounting format for accounts receivable, commercial bills receivable, and methods of calculating the reserve for doubtful debts. The types of value that are applied to various types of receivables of the enterprise are analysed. The possibilities and advantages of using motivational discounts, commercial bills receivable as tools for optimizing the structure of receivables are defined. Proposed components of the process of managing receivables and optimizing the duration of the credit cycle: development of a policy for providing commodity credit (deferred payment); establishing a credit rating for buyers by establishing their creditworthiness; setting a lending limit depending on the rating; establishment of standard credit terms; establishment of standard discounts; analysis of receivables; working with overdue receivables. A comparative analysis of the methods of reserving doubtful receivables and the international format of reflecting in accounting the write-off of bad debts and the accrual of bad debts reserve are provided. It was determined that the use of incentive discounts can significantly accelerate the repayment period of accounts receivable and release funds on time. In order to strengthen the financial security of the enterprise, it is proposed to apply methods already existing in international practice - factoring as an opportunity to quickly convert doubtful debt into cash; the use of commercial bills as a prolongation of payment deferrals with the receipt of additional interest income, trade motivational discounts as an incentive to speed up the payment of debtors' accounts.
Accounting and management of receivables to strengthen the financial security of the enterprise
Keywords: облік; accounting; дебіторська заборгованість; accounts receivable; сумнівна заборгованість; doubtful debts; резерв безнадійних боргів; bad debt reserve; вексель; promissory note; рахунки до отримання; accounts receivable